Optimal systems and group invariant solutions for a model arising in financial mathematics - Nteumagne, Bienvenue Feugang; Moitsheki, Raseelo J. (Mathematical Modelling and Analysis, 2009)
We consider a bond‐pricing model described in terms of partial differential equations (PDEs). Classical Lie point symmetry analysis of the considered PDEs resulted in a number of point symmetries being admitted. The one‐dimensional optimal system of subalgebras is constructed. Following the symmetry reductions, we determine the group‐invariant solutions.First published online: 14 Oct 2010